2004
DOI: 10.1111/j.1365-2303.2004.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Follicular variant of papillary thyroid carcinoma – a cytological study

Abstract: The cytological diagnosis of classical papillary carcinoma is easily established based on the characteristic architectural and nuclear features. However, the follicular variant of papillary thyroid carcinoma(FVPTC) poses a diagnostic challenge. In this study we analysed the cytological features of 14 histopathologically proven cases of FVPTC. We inferred that a combination of architectural features such as follicles and syncytial clusters and nuclear features, viz grooves, pseudoinclusions and enlarged nuclei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…15,16 Absence of papillary fragments was used by Baloch et al 8 to differentiate between FVPC and classical papillary carcinoma; however, papillary fragments have been documented in cases of FVPC in some recent studies. 19,20 In the present study, although papillary fragments were absent from a large majority of our cases (40 of 59, or 67.79%), they were present in the remaining cases and were readily identifiable in 5 cases. Nuclear grooves, chromatin clearing and INCI are the mainstay in the diagnosis of classical papillary carcinoma.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…15,16 Absence of papillary fragments was used by Baloch et al 8 to differentiate between FVPC and classical papillary carcinoma; however, papillary fragments have been documented in cases of FVPC in some recent studies. 19,20 In the present study, although papillary fragments were absent from a large majority of our cases (40 of 59, or 67.79%), they were present in the remaining cases and were readily identifiable in 5 cases. Nuclear grooves, chromatin clearing and INCI are the mainstay in the diagnosis of classical papillary carcinoma.…”
Section: Discussionmentioning
confidence: 80%
“…Most other authors have reported a high incidence of nuclear grooves. 2,4,9,20 In the present study we identified nuclear grooves in 54 of 59 cases, but they were prominent in only 18 cases and very focal in 10. INCI have been reported to a lesser extent as compared to nuclear grooves in most studies.…”
Section: Discussionmentioning
confidence: 83%
“…This is a problem addressed by several previous publications [109,110,111,112,113,114] that reflect the fuzzy understanding and interobserver and intraobserver variations in evaluating the nuclear features indicating the PTC diagnosis. Not even our usage of polychrome staining over several years in addition to the MGG and HE recommended by Yang and Greenebaum [111] prevented us from underdiagnosing the nuclear features.…”
Section: Discussionmentioning
confidence: 88%
“…[2] Thyroid lesions with follicular growth pattern are composed of a wide range including benign adenomatous nodule, Follicular Thyroid Adenoma (FTA), Follicular Thyroid carcinoma (FTC) and Follicular variant of Papillary Thyroid Carcinoma (FVPTC). [3][4][5] FTA, FTC and FVPTC are well encapsulated lesions sharing many imaging, cytologic and histologic features [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%